Impact of Baseline Terms on the Course of Critical Paths and Time Buffers in the Modified Goldratt’s Method - Połoński M.; Pruszyński K. (Archives of Civil Engineering, 2013)
The introduction of a baseline term to the dependency network most often results in a change, break and/or generation of a new sequence of critical path, depending on the type of such a baseline term and the exact date selected. Each of those situations has an impact on the location or need to include new time buffers in the modified Goldratt’s method. The purpose of this article was to identify possible effects brought by declaration of each type of baseline term and to point out actions to be taken in each case. It must be noted that guidelines provided should in each individual case be adapted to the specific character of schedule changes caused by implementation of the relevant baseline term. The example presented herein exemplifies one of such solutions to be implemented as a result of break of the critical path and need to introduce new time buffers.